(untitled) (Alternautas, 2022)
Norma Giarracca had a deep and wide trajectory as a social researcher, especially as a rural sociologist. But she mostly published in Spanish, and thus her work is not readily accessible to many readers around the world. I am deeply grateful to the compañeras and compañeros of Alternautas to offer other researchers the opportunity to access the many insights of Norma’s work. Her winding trajectory hints at her intellectual curiosity and her openness to new perspectives – she was also a fan of music and often sought to connect social research and artistic expressions, for instance, asking her son Julián Teubal to join in research trips and then using his pictures on exhibits during book presentations or academic events, or coordinating a study linking music and protest (Bidaseca, Lapegna, Mariotti, et al. 2001). Norma was deeply committed to social justice and had the utmost respect and appreciation for the “subjects” of her research. She often had brusque manners, but also an immense generosity. She fitted many worlds in the relatively small world of rural sociology and made its branches extend beyond disciplines, countries, and perspectives. She has been sorely missed since 2015, but the seeds she planted keep sprouting and growing.